Comparative Analysis of Efficacy, Toxicity, and Patient-Reported Outcomes in Rectal Cancer Patients Undergoing Preoperative 3D Conformal Radiotherapy or VMAT - Regnier, Antonia; Ulbrich, Jana; Münch, Stefan; Oechsner, Markus; Wilhelm, Dirk; Combs, Stephanie E.; Habermehl, Daniel (Frontiers in Oncology, 2017)
Background Locally advanced rectal cancer patients are usually treated within a multimodal therapy regime, in which the tumor resection plays the major role. This treatment ideally includes 5-fluorouracile based chemoradiation (CRT) leading to significantly improved local control rates. Local therapy as radiotherapy (RT) is required to be adapted referring to side effects and efficacy. Purpose of this study is the comparison of dosimetric parameters, acute and late tocixity and quality of life in terms of patient reported outcome (PRO) in patients treated with VMAT or 3D-conformal radiotherapy (3DCRT) for locally advanced rectal cancer. Methods Pelvic RT for locally advanced rectal cancer was performed with a prescription dose of 45 Gy in 1.8 Gy per fraction, 50.4 Gy in 1.8 Gy per fraction or 50 Gy in 2 Gy per fraction. Chemotherapy included 5FU or 5FU/Oxaliplatin or Capecitabine-based RT. Acute and late toxicity were evaluated via National Institute Common Terminology Criteria for Adverse Events version (CTCAE) v4.03 and the Scoring System Late effects of Normal Tissue. Quality of life was established via EORTC QLQCR29. Results After a median follow up of 38 months (VMAT) and 78 months (3DCRT) there was no significant difference in progression-free-survival (p=0,85) but a significant difference in overall survival (p=0,032). Regarding dose volume parameters, patients treated with VMAT plans had a lower V20 of the bladder than 3D-CRT treated patients (p=0.004). VMAT plans can also reduce Dmean of the right (p=0.002) and left (p<0.001) femoral head. Acute side effects between the VMAT and 3DCRT patients showed no significant difference. But concerning long term effects VMAT treated patients had a significant lower appearance of high grade anal incontinence (p=0.032). Quality of life (PRO) showed no significant different between the patients except of hair loss and worrying about weight. Conclusion VMAT treatment of LARC in preoperative CRT revealed a reduction of dose to OARs as bladder and femoral heads. However no changes in acute and long term toxicity profiles were detectable. For late toxicity and quality of life data longer follow up times are required.